Building Green Purchase Intention: The Mediating Role of Green Trust on Green Packaging and Green Product of Mountoya - Muhamad Dani Fiqri; May Dedu; Tiara Muthiarsih (Indonesian Journal of Business Analytics, 2026)
The purpose of this study is to test the role of green trust in mediating the influence of green packaging and green products on green purchase intention in Mountoya bottled drinking water consumers. Increasing environmental awareness and competition in the bottled water industry are important backgrounds in understanding the factors that encourage environmentally friendly purchasing intentions. This study uses a quantitative approach by collecting data from 170 Mountoya consumers in Cirebon City using purposive sampling techniques through a structured questionnaire. Data analysis was carried out using the Partial Least Square (PLS) method with the help of SmartPLS software. The results of the study show that green packaging and green products have a positive and significant effect on green trust, and green trust has a positive effect on green purchase intention. Other findings show that green packaging does not have a direct effect on purchase intention, but its effect becomes significant when mediated by green trust, while green products have a significant effect both directly and through green trust. These findings confirm the importance of consumer trust in encouraging environmentally friendly purchase intentions.